PERKEMBANGAN PENDAFTARAN JAMINAN FIDUSIA DARI SISTEM MANUAL KE SISTEM ONLINE SERTA HAMBATAN-HAMBATANNYA - DITA SABILA (PREMISE LAW JURNAL, 2018)
People’s rapid demand for registering fiduciary collateral has caused the government to make it by online. The launching of fiduciary by online is a concrete effort to provide positive contribution to strengthen movable property as a collateral system in Indonesia. In practice, however, many obstacles faced by a Notary in registering fiduciary collateral by online. The objective of the research is to find out whether registering fiduciary collateral by online has been in accordance with the prevailing regulations, how about the development of fiduciary collateral registration from manual to online system, and how about the obstacles in registering fiduciary collateral by online and the solution.Keywords: Fiduciary Collateral, Fiduciary Registration, Online Fiduciary